Peningkatan Keterampilan Menulis Bahasa Inggris melalui Triple-R Method - Khasanah, Marisatul (Paedagogie, 2019)
This research aimed at enhancing students’ writing skills through Triple-R Method. This Classroom Action Research was conducted in SMPN 2 Banjarnegara to 32 students of Class VIIC as the participants. Data of students’ writing were gathered through tests while the learning process was captured through observation. Then they were analyzed descriptively. The results revealed the writing skills increased from 63.59 in Pre-Cycle, 70.0 in Cycle I, ten 72.81 in Cycle II. Hence, Triple-R Method could enhance students’ writing skills.